BUSINESS INTELLIGENCE MATURITY ASSESSMENT: A CASE STUDY ON AN INDONESIAN AUTOMOTIVE COMPANY - Ajie Tri Hutama; Achmad Nizar Hidayanto; Ryan Randy Suryono (Jurnal Teknoinfo, 2023)
The increasing volume of data, systems that became more complex, and the need for tools to collect, store and process data have driven automotive companies to implement Business Intelligence (BI) system. Successful adoption of BI technology enables organizations to have higher business effectiveness and IT investment. In the organization that newly adopt BI technology, BI Project often failed. In organizations that already implement BI system, also often unable to get full benefits of the system. Maturity assessment is a method for assessing to which maturity level of human resources, organizational processes, and technology is implemented in an organization or company. By conducting it will provide the company with an overview of where the current maturity level is and provides an overview of the roadmap for achieving a higher maturity level where a higher level results in good business effectiveness. Investigate the maturity level of BI system focusing on an Indonesian automotive company and which parameter need to be improved are the objectives of this study. For BI maturity assessment in an Indonesian automotive company, we use the Business Intelligence maturity model (biMM) [1]. The study found that the overall organization’s maturity level to adopt BI system is 3.05 which means company is on the third stage biMM: information integration. Technology maturity is on the lowest point with an average of 2.87 point, Functionality is in the middle with 2.94 point, and Organization have highest point with 3.26 point. The company can improve on SLA Awareness, Data Management, and Data Architecture while retaining the performance of BI Strategy & BI Governance.